Ferroportin-Dependent Iron Homeostasis Protects against Oxidative Stress-Induced Nucleus Pulposus Cell Ferroptosis and Ameliorates Intervertebral Disc Degeneration In Vivo. (10th February 2021) - Lu, Saideng; Song, Yu; Luo, Rongjin; Li, Shuai; Li, Gaocai; Wang, Kun; Liao, Zhiwei; Wang, Bingjin; Ke, Wencan; Xiang, Qian; Chen, Chao; Wu, Xinghuo; et al.
Abstract : Ferroptosis is a specialized form of regulated cell death that is charactered by iron-dependent lethal lipid peroxidation, a process associated with multiple diseases. However, its role in the pathogenesis of intervertebral disc degeneration (IVDD) is rarely investigated. This study is aimed at investigating the role of ferroptosis in oxidative stress- (OS-) induced nucleus pulposus cell (NPC) decline and the pathogenesis of IVDD and determine the underlying regulatory mechanisms. We used tert-butyl hydroperoxide (TBHP) to simulate OS conditions around human NPCs. Flow cytometry and transmission electron microscopy were used to identify ferroptosis, while iron assay kit, Perl's staining, and western blotting were performed to assay the intracellular iron levels. A ferroportin- (FPN-) lentivirus and FPN-siRNA were constructed and used to explore the relationship between FPN, intracellular iron homeostasis, and ferroptosis. Furthermore, hinokitiol, a bioactive compound known to specifically resist OS and restore FPN function, was evaluated for its therapeutic role in IVDD both in vitro and in vivo . The results indicated that intercellular iron overload plays an essential role in TBHP-induced ferroptosis of human NPCs. Mechanistically, FPN dysregulation is responsible for intercellular iron overload under OS. The increase in nuclear translocation of metal-regulatory transcription factor 1 (MTF1) restored the function of FPN, abolished the intercellular iron overload, and protected cells against ferroptosis. Additionally, hinokitiol enhanced the nuclear translocation of MTF1 by suppressing the JNK pathway and ameliorated the progression of IVDD in vivo . Taken together, our results demonstrate that ferroptosis and FPN dysfunction are involved in the NPC depletion and the pathogenesis of IVDD under OS. To the best of our knowledge, this is the first study to demonstrate the protective role of FPN in ferroptosis of NPCs, suggesting its potential used as a novel therapeutic target against IVDD.